The Effect of Government Expenditure on Education and Health Sectors on Poverty Rate (Study at Kuningan Regency, West Java) - Laksmi, Ayu Chairina; Puteri, Saefah Auliyandini (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
Poverty is the main problem included in the agenda of the national development design. In 2022, Kuningan regency has the highest poverty rate among other regions in West Java. The study aims to determine the influence of government expenditure on education and health sectors on the poverty rate in Kuningan regency for the year of 2019-2022. This research describes the effect of government programs such as National Health Insurance (JKN) and Program Indonesia Pintar (PIP) on poverty rate in Kuningan regency, West Java. This research employed quantitative approach and multiple linear regression analysis using SPSS 25 software. The research used secondary data sourced from the Social Service, Education Office, and Health Office of Kuningan regency, West Java province. The results of this study show that the government expenditure on the education and health sectors has a negative and significant effect on the poverty rate in 32 sub-districts of Kuningan regency.